Contentious Politics di antara Dua Kota di Pantai Barat Norwegia Terkait dengan Kebijakan Pelayanan Kesehatan Bersama - Soeseno, Nuri (Jurnal Politik, 2015)
The establishment (plan) of a common hospital for Nordmøre and Romsdal is not the right policy nor a solution to end the long bickering between Kristiansund and Molde; it is a beginning of a wider contentious politics in Nordmøre and Romsdal Province. The undemocratic appointment of Hjelset (Molde) as the site for a new hospital in Nordmøre and Romsdal is not just a natural ‘consequence’ of the adoption of the new perspective in healthcare services in Norway and part of the agenda for the development of a more effective, professional and future oriented healthcare services in Norway, but also an outcome of the long contentious politics between the two towns and regions in the same province.